“Desarrollo de un mapa espectral de cobertura móvil en la Universidad Técnica Estatal de Quevedo” - Arboleda Chalco , Daniel Josué (2023)
This research project focuses on improving mobile network coverage at the "Manuel Haz Álvarez" and "La María" campuses of the Universidad Técnica Estatal de Quevedo. A digital map has been developed using spectral diagramming to identify areas with higher and lower mobile network coverage in these university environments. Data from various sources, including information from communication service providers and previous studies, were collected for this purpose. The obtained results enable informed decisions regarding the expansion of telecommunications infrastructure, aiming to enhance the quality of communication services and the technological experience of the university community. This research project focuses on improving mobile network coverage at the "Manuel Haz Álvarez" and "La María" campuses of the Universidad Técnica Estatal de Quevedo. A digital map has been developed using spectral diagramming to identify areas with higher and lower mobile network coverage in these university environments. Data from various sources, including information from communication service providers and previous studies, were collected for this purpose. The obtained results enable informed decisions regarding the expansion of telecommunications infrastructure, aiming to enhance the quality of communication services and the technological experience of the university community.